TINJAUAN PERILAKU BIROKRASI APARATUR PEMERINTAH DAERAH DI ERA OTONOMI DAERAH - Deden Haria Garmana (Journal Of Regional Public Administration (JRPA), 2016)
In general the behavior of bureaucratic apparatus of government is the result of interaction between individuals and their environment. So even structurally, government bureaucracy should be accommodated in the improvement of the characteristics, as well as the capability and capacity of the state apparatus as a servant of the man of society and public services actor. The realization of the bureaucratic apparatus of government behavior that ideal is bureaucratic apparatus that has a moral, ethical and attitude is commendable and exemplary. Therefore, the behavior of bureaucratic apparatus at least be formed by five norms, ie norms positions, social norms, norms of the profession, family norms and other norms (legal, decency and moral norms).